Vibrational properties of graphene fluoride and graphane - Peelaers, H. (2011)
The vibrational properties of graphene fluoride and graphane are studied using ab initio calculations. We find that both sp3 bonded derivatives of graphene have different phonon dispersion relations and phonon densities of states as expected from the different masses associated with the attached atoms of fluorine and hydrogen, respectively. These differences manifest themselves in the predicted temperature behavior of the constant-volume specific heat of both compounds.